2006
DOI: 10.1590/s1413-86702006000400010
|View full text |Cite
|
Sign up to set email alerts
|

Audiological and electrophysiological evaluation of children with acquired immunodeficiency syndrome (AIDS)

Abstract: We examined the peripheral auditory system and the auditory brainstem pathway of children with Acquired Immunodeficiency Syndrome (AIDS). One hundred and one children, 51 with AIDS diagnosis and 50 normal children were evaluated. Audiological assessment included immittance measures, pure tone and speech audiometry and auditory brainstem response (ABR). The children with AIDS more frequently had abnormal results than did their matched controls, presenting either peripheral or auditory brainstem impairment. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 16 publications
3
27
0
1
Order By: Relevance
“…However, it is alarming that this hearing loss may progressively compromise the affected regions, thus suggesting the requirement for further investigations in children with HIV/AIDS. The present study showed a higher frequency of sensorineural and conductive hearing loss in Group B children (aged 5 years or older) compared to younger children (Table 4), however, children with HIV typically experience conductive hearing loss secondary to middle ear abnormalities (18) .…”
Section: Discussionmentioning
confidence: 38%
See 2 more Smart Citations
“…However, it is alarming that this hearing loss may progressively compromise the affected regions, thus suggesting the requirement for further investigations in children with HIV/AIDS. The present study showed a higher frequency of sensorineural and conductive hearing loss in Group B children (aged 5 years or older) compared to younger children (Table 4), however, children with HIV typically experience conductive hearing loss secondary to middle ear abnormalities (18) .…”
Section: Discussionmentioning
confidence: 38%
“…A previous study (18) showed a higher prevalence of hearing abnormality in children with HIV/AIDS aged between 3 and 6 years compared to older children between 7 and 10 years. In another study (20) , the prevalence of hearing loss in patients with HIV/AIDS aged between 6 months and 5 years was 33%, which was significantly lower than that observed in this study (85%) in children younger than 5 years.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…[10][11] Audiological testing consisted of distortion product evoked otoacoustic emissions (DPOAE) and behavioral observation audiometry (BOA), with reassessments as needed.…”
Section: Methodsmentioning
confidence: 99%
“…5,7 The Joint Committee on Infant Hearing (JCIH) has proposed risk indicators to be used internationally, 8,9 supplemented by studies to adapt these indicators locally, for instance to the Brazilian context. 10,11 The purpose of this study was to verify the prevalence of hearing impairment and to correlate it with risk indicators in neonates born and monitored at a tertiary hospital.…”
Section: Introductionmentioning
confidence: 99%